ENVIRONMENTAL OBLIGATIONS OF RUSSIAN ORGANIZATIONS: THE PARADOX OF INFORMATION DISCLOSURE DEPENDING ON APPLICABLE STANDARDS - O. V. Zhukova (Вестник университета)
The article сarries out an analysis of the reflection of the consequences of environmental disasters and the corresponding preventive measures on the example of the consolidated financial statements of the Group of mining and metallurgical companies “Norilsk Nickel” and the accounting (financial) statements of JSC “Norilsk-Taimyr energy company” (NTEK), which is part of this group. The paper pays particular attention to the relationship between recognized environmental protection obligations and applicable standards for the preparation  of accounting (financial) statements of commercial organizations and consolidated statements of groups that include these business entities. Based on the results of the study, the author formulates priority proposals to  improve the Russian system of normative regulation of disclosure of information about environmental obligations  in accounting (financial) statements.